Mosquito mass rearing: who’s eating the eggs? - Yamada Hanano; Kraupa Carina; Lienhard Charles; Parker Andrew Gordon; Maiga Hamidou; de Oliveira Carvalho Danilo; Zheng Minlin; Wallner Thomas; Bouyer Jeremy (Parasite, 2019)
For the sterile insect technique, and other related biological control methods where large numbers of the target mosquito are reared artificially, production efficiency is key for the economic viability of the technique. Rearing success begins with high quality eggs. Excess eggs are often stockpiled and stored for longer periods of time. Any pests that prey on these eggs are detrimental to stockpiles and need to be avoided. Psocids of the genus Liposcelis (Psocoptera, Liposcelididae) are common scavengers consuming various types of organic material that are distributed globally and thrive in warm damp environments, making insectaries ideal habitats. In this short report, we investigated the species that has been found scavenging stored mosquito eggs in our insectary and identified it to be Liposcelis bostrychophila Badonnel, 1931. Additional observations were made to determine whether these predators indeed feed on mosquito eggs, and to suggest simple, effective ways of avoiding infestation.